Proses Ta'dib sebagai penguatan aplikasi pendidikan Islam di Indonesia: Pendekatan Systematic Literature Review - Rachmawati, Depy Eka; Purwandari, Eny (Tawazun: Jurnal Pendidikan Islam, 2022)
Applications in Islamic education cannot be separated from the challenges that have an impact on the quality of the students. This challenge, if left unchecked, will further distance itself from its goal, to form Al Insan Al Kamil. So the concept of ta'dib becomes an offer to strengthen the application of Islamic education. This article aims to explore the process of ta'dib as a solid foundation that strengthens the application of Islamic education. The method used in this article is qualitative with a systematic literature review approach. Relevant articles were collected from the google scholar portal through the PRISMA (Preferred Reporting Item for Systematic Reviews and Meta-analyses) flow. Then a descriptive content analysis was carried out. The results found indicate that the thing that is prioritized in the ta'dib process is the integration of knowledge, charity, and morals in everyday life. The ta'dib process is a two-way process between educators and students. This process emphasizes good examples and habituation. Its application is not only in schools setting but is also sustainable in the family and society in general. Abstrak Aplikasi dalam pendidikan Islam tidak terlepas dari tantangan-tantangan yang berdampak pada kualitas peserta didiknya. Tantangan ini jika dibiarkan akan semakin menjauhkan dari tujuannya, untuk membentuk Al Insan Al Kamil. Sehingga konsep ta'dib menjadi sebuah tawaran untuk menguatkan aplikasi pendidikan Islam. Artikel ini bertujuan untuk menelusuri proses ta'dib sebagai landasan kokoh yang menguatkan aplikasi dari pendidikan Islam. Metode yang dilakukan dalam artikel ini yaitu kualitatif dengan pendekatan systematic literature review. Artikel-artikel yang relevan dikumpulkan dari portal Google scholar melalui alur PRISMA (Preferred Reporting Item for Systematic Reviews and Meta-analyses). Kemudian dilakukan analisis isi secara deskriptif. Hasil yang ditemukan menunjukkan bahwa hal yang diutamakan dalam proses ta'dib ialah integrasi antara ilmu, amal dan akhlak dalam kehidupan sehari-hari. Proses ta'dib merupakan proses dua arah antara pendidik dengan peserta didik. Proses ini menekankan pada keteladanan dan pembiasaan yang baik. Aplikasinya tidak hanya di-setting sekolah, namun juga berkelanjutan di lingkungan keluarga dan masyarakat secara umum.